The New Jersey medical school - Schwartz, Robert A. (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2005)
The New Jersey Medical School (NJMS) was the first medical school in the stateof New Jersey. Its creation repuired the vision and support of many, including a group of leaders at the Jersey City Medical Center, century old Seton Hall University and the Archdiocese of Newark. Chartered in 1954 as Seton Hall College of Medicine, it opened its doors in Jersey City in 1956. Itwas renamed as the New Jersey College of Medicine (1965-1970), and since 1970 as New Jersey Medical School.
Keywords: Faculty, Medical; Fakulteta medicinska; History; New Jersey; Organization And Administration; Trends; United States; United States of America; ZDA